Pentagon Fraud Factors: Impact and Implications on Cash Theft by Employees of Bank BPRS Bhakti Sumekar Sumenep - Alamsyah, Mohammad Ilham Catur; Alfian, Nurul; Rahayu, Runik Puji (Universitas Madura, 2025)
In the world of economics, fraud is a problem that is still inherent and growing in the global community to this day. Fraud can be found not only in small organizations but also in large companies are not immune to fraud within them. Pentagon fraud is the result of the development of previously discovered fraud theories. Starting from the fraud triangle theory with the elements of pressure, rationalization, and opportunity which then continued to develop into the fraud pentagon. The purpose of this study is to determine whether pressure, opportunity, rationalization, ability and arrogance influence cash theft. This type of research is quantitative research. The data source used is primary data. The data collection technique used a questionnaire. The population in this study were employees of Bank BPRS Bhakti Sumekar Sumenep. Sampling in this study used a purposive sampling technique. Data analysis techniques used are Validity Test, Reliability Test, Descriptive Statistics, Classical Assumption Test, Multiple Linear Analysis, Coefficient of Determination Test, T-Test, F-Test. Data management used the SPSS program. The results of this study indicate that partially pressure has an effect on cash theft, opportunity has an effect on cash theft, rationalization has no effect on cash theft, ability has an effect on cash theft, arrogance has an effect on cash theft.